STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BAGI ANAK BERKEBUTUHAN KHUSUS - Saiful Akhyar Lubis; Yusnaili Budianti; Zulpadlan Zulpadlan (Universitas Muria Kudus, 2022)
The purpose of this study is to describe the learning strategy of Islamic Religious Education for children with special needs at the ABC Melati Aisyiyah Special School (SLB) Tembung.The research method used is descriptive qualitative with data collection techniques using observation, interviews, and documentation. This research was carried out from July to September 2021. The data analysis techniques used were data reduction, data presentation and conclusion drawing. While the technique of guaranteeing the validity of the data using triangulation techniques.The results showed that SLB ABC Melati Aisyiyah Tembung in the learning process used demonstration learning strategies and fun learning strategies with Play, Singing, and Stories (BMC). Several obstacles were experienced, especially in technical problems, such as the lack of teaching materials, the lack of learning media used, and the incompatibility of the lesson plans with implementation practices in the field.